2002
DOI: 10.1046/j.1472-8206.2002.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amitriptyline on gastric ulceration

Abstract: Amitriptyline significantly inhibited alcohol, aspirin, indomethacin and cold-restraint stress-induced ulceration. Secretory studies conducted in pyloric-ligated rats revealed that the drug, at the doses employed, significantly reduced total acidity and protein content. However, significant reductions of the gastric volume were only observed at the highest dose of the drug. In another set of experiments, when 50% alcohol (v/v) was administered to the pyloric-ligated rats pretreated with amitriptyline, it was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
11
0
4
Order By: Relevance
“…Apart from these factors, depression with psychotic and somatic symptoms has been seen in patients with GIS disease [10]. Clinical studies on this issue have demonstrated that anxiolytic and antidepressant drug therapy is useful in ulcerative patients with depression [11]. Because antidepressant drugs are useful for clinical ulcer treatment, one may think that ulcer pathogenesis is particularly connected with depression.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these factors, depression with psychotic and somatic symptoms has been seen in patients with GIS disease [10]. Clinical studies on this issue have demonstrated that anxiolytic and antidepressant drug therapy is useful in ulcerative patients with depression [11]. Because antidepressant drugs are useful for clinical ulcer treatment, one may think that ulcer pathogenesis is particularly connected with depression.…”
Section: Introductionmentioning
confidence: 99%
“…34) Sen et al suggested that amitriptyline's antiulcer eŠect might be attributable to LoAZ inhibition in indomethacin-induced ulcers, leucotriene ( LT ) blockade and 5-LoAZ inhibition in ethanol-induced ulcers, and central and peripheral anti-LT activity in cold-stress-induced ulcers. 32) Many experimental studies have shown that antidepressant drugs elicit antiulcer eŠects by reducing histamine secretion from mast cells, inhibiting gastric acid secretion, and blocking LT (LTC 4 , D 4 , and E 4 ) receptors. 32,35) Apart form these factors and mechanisms, other studies have shown that the important primary factor in indomethacin-induced gastric damage is the reactive oxygen species (ROS) mediated lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…32) Many experimental studies have shown that antidepressant drugs elicit antiulcer eŠects by reducing histamine secretion from mast cells, inhibiting gastric acid secretion, and blocking LT (LTC 4 , D 4 , and E 4 ) receptors. 32,35) Apart form these factors and mechanisms, other studies have shown that the important primary factor in indomethacin-induced gastric damage is the reactive oxygen species (ROS) mediated lipid peroxidation. 36) Also several antidepressants such as tricyclic antidepressants, tiyaneptine and mirtazapine have been reported to exert antioxidative eŠect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, postmortem interpretation of chronic abuse and related physical disorders is often very difficult due to a lack of specific findings. Previous studies showed various pathological findings in drug abusers, which included cardiopulmonary abnormalities [1], myocardial hypertrophy [2] and cerebral hemorrhage [3] in amphetamine abusers and gastric ulcers [4], atrophy of the hippocampus [5] and brainstem ischemia [6] in psychotropic drug abusers. However, there appears to be few investigations of the human endocrine system in drug abusers from a medicolegal aspect [7].…”
Section: Introductionmentioning
confidence: 99%